Comprehensive metabolomics to evaluate the impact of industrial processing on the phytochemical composition of vegetable purees. (1st February 2015) - Lopez-Sanchez, Patricia; de Vos, R.C.H.; Jonker, H.H.; Mumm, R.; Hall, R.D.; Bialek, L.; Leenman, R.; Strassburg, K.; Vreeken, R.; Hankemeier, T.; Schumm, S.; van Duynhoven, J.
Highlights: Processing effect on phytochemical composition of vegetable purees was investigated. Comprehensive metabolomics provided broad insight into processing effects. Phytochemical composition was mostly affected by the order of blending and heating. Heating prior to blending resulted in more vitamins and less oxidation products. Activity of endogenous plant enzymes is likely key to final metabolite composition. Abstract: The effects of conventional industrial processing steps on global phytochemical composition of broccoli, tomato and carrot purees were investigated by using a range of complementary targeted and untargeted metabolomics approaches including LC–PDA for vitamins, 1 H NMR for polar metabolites, accurate mass LC–QTOF MS for semi-polar metabolites, LC–MRM for oxylipins, and headspace GC–MS for volatile compounds. An initial exploratory experiment indicated that the order of blending and thermal treatments had the highest impact on the phytochemicals in the purees. This blending-heating order effect was investigated in more depth by performing alternate blending-heating sequences in triplicate on the same batches of broccoli, tomato and carrot. For each vegetable and particularly in broccoli, a large proportion of the metabolites detected in the purees was significantly influenced by the blending-heating order, amongst which were potential health-related phytochemicals and flavour compounds like vitamins C and E, carotenoids, flavonoids, glucosinolates and oxylipins. Our metabolomics data indicates that during processing the activity of a series of endogenous plant enzymes, such as lipoxygenases, peroxidases and glycosidases, including myrosinase in broccoli, is key to the final metabolite composition and related quality of the purees.